2021
DOI: 10.1021/acs.jpclett.1c00406
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Electrostatic Effect on Redox Potential by Positive Charges in a Catalyst Microenvironment

Abstract: Charged functional groups in the secondary coordination sphere (SCS) of a heterogeneous nanoparticle or homogeneous electrocatalyst are of growing interest due to enhancements in reactivity that derive from specific interactions that stabilize substrate binding or charged intermediates. At the same time, accurate benchmarking of electrocatalyst systems most often depends on the development of linear free-energy scaling relationships. However, the thermodynamic axis in those kinetic–thermodynamic correlations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…123,124 In a recent contribution, Berben and co-workers studied electrostatic effects arising from the incorporation of positive charge onto an [Fe 4 N(CO) 12 ] À cluster through the incorporation of methyl-1,3,5-triaza-7-phosphaadamantane ( Me PTA + ) (Scheme 44). 125 Further, they observed that incorporation of four positively charged groups in the SCS manifested in a change of ca. 600 mV in reduction potential.…”
Section: Cationic and Anionic Ligandsmentioning
confidence: 99%
“…123,124 In a recent contribution, Berben and co-workers studied electrostatic effects arising from the incorporation of positive charge onto an [Fe 4 N(CO) 12 ] À cluster through the incorporation of methyl-1,3,5-triaza-7-phosphaadamantane ( Me PTA + ) (Scheme 44). 125 Further, they observed that incorporation of four positively charged groups in the SCS manifested in a change of ca. 600 mV in reduction potential.…”
Section: Cationic and Anionic Ligandsmentioning
confidence: 99%
“…6 , 7 The molecular nature of these clusters allows us to gain detailed structural insight into the electrocatalytic active species and into the overall mechanism occurring in the catalyst microenvironment. 8 In this sense, the study of larger and larger molecular clusters such as HNMCCs represents an exciting frontier that could create a bridge to contemporary nanomaterials for electronic and electrochemical applications. 9 13 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 The molecular nature of these clusters allows us to gain detailed structural insight into the electrocatalytic active species and into the overall mechanism occurring in the catalyst microenvironment. 8 In this sense, the study of larger and larger molecular clusters such as HNMCCs represents an exciting frontier that could create a bridge to contemporary nanomaterials for electronic and electrochemical applications. 9−13 The redox behavior of HNMCCs has been investigated by electrochemical and spectroelectrochemical methods, and recently, we reported the first two cases of multivalence in large Ni−Pd molecular nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scaling relationship between E pc,1 versus ν CO bands in isostructural Mn(bpy) systems measured in an ACN solution from literature reports and the data presented here was used to probe the combined inductive and electrostatic effects imparted by MIC ligands. 50 Interestingly, C MIC-py exhibited the same trend as R-bpy (R = [4,4′]-H, -OH, -tertbutyl, and -methyl) and C triazol-py, whereas N MIC-py is offtrend by ∼180 mV (Figure 6 and Scheme S1). 6,23,43,51 The substitution of alkyls for aryls along the MIC fragment is also known to play a significant role in the π-accepting ability; however, to the best of our knowledge, no standard procedure or model has been introduced to analyze the electronic properties of these ligand types.…”
Section: ■ Introductionmentioning
confidence: 88%